1983
DOI: 10.1203/00006450-198302000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Circulatory Responses to Methionine-Enkephalin

Abstract: Summarydescending aorta and inferior vena cava, respectivelv. The fetalThe cardiovascular and respiratory effects of the naturally occurring endogenous opiate, methionine-enkephalin, were studied in 23 fetal sheep, five newborn lambs, 15 pregnant sheep, and four nonpregnant ewes. The opiate peptide produced dose-dependent decreases in heart rate and blood pressure in fetal and neonatal lambs but increased heart rate and blood pressure followed immediately by decreased heart rate and blood pressure in pregnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Intravenous administration of methio nine-enkephalin in the fetus has been shown to produce an immediate, profound brady cardia lasting 10-30 s which can be pre vented by opioid receptor blockade with nal oxone or parasympathetic blockade with atropine (muscarinic) and trimethaphan (nic otinic) [17,18]. Thus, it is unlikely that the slight (10%) additional decrease in heart rate observed following naloxone administration in the asphyxiated fetus [11] is the result of opioid receptor blockade alone.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous administration of methio nine-enkephalin in the fetus has been shown to produce an immediate, profound brady cardia lasting 10-30 s which can be pre vented by opioid receptor blockade with nal oxone or parasympathetic blockade with atropine (muscarinic) and trimethaphan (nic otinic) [17,18]. Thus, it is unlikely that the slight (10%) additional decrease in heart rate observed following naloxone administration in the asphyxiated fetus [11] is the result of opioid receptor blockade alone.…”
Section: Discussionmentioning
confidence: 99%
“…Mus carinic blockade with atropine and gan glionic blockade with either hexaméthonium or chlorisondamine virtually eliminated the HR changes and suggest that enkephalin acts at either the parasympathetic ganglia or at a central autonomic site. La Gamma et al [ 14] demonstrated similar responses which they believed were compatible with a central site of action. However, the absence of HR slow ing following intracisternal administration of endogenous opioids suggests that the central autonomic centers may not participate in this response in the fetus.…”
Section: Discussionmentioning
confidence: 51%
“…Recently, developmental changes have been noted in opioid receptor concentration and affinity during the post natal period [12,13]. La Gamma et al [14] have demonstrated depression of heart rate (HR) and blood pressure (BP) following in travenous meth-enkephalin in the sheep fe tus, but tachycardia and hypertension in the adult. The present investigation was under taken to assess the effects of both central ner vous and intravenous administration of meth-enkephalin and P-endorphin on HR, BP and fetal breathing movements (FBM) in the chronically catheterized fetal lamb in utero.…”
Section: Introductionmentioning
confidence: 99%
“…Both central and peripheral infusions of met-enkephalin in fetal sheep are shown to have significant effects on heart rate, blood pressure and fetal breathing move ments [3,18]. These effects are eliminated by autonomic blockade and blunted by nal oxone.…”
Section: Discussionmentioning
confidence: 96%